The effect of layer compaction on the strength of cast concrete structures - M.S. Egamberdiev (Genius Journals, 2022)
According to the results of scientific research, there are definite times when concrete compaction occurs on the basis of experiments. These times also of course depend on the amount of cement in the concrete. No matter how much or how much cement is added to the concrete, the exact (10-second) compaction time determined experimentally must be introduced, as excessive compaction will result in the loss of cement in the mix in powder form. You can see the condition of the accumulated gravel or crushed stones. In this case, the water from the top layer to the bottom layer is very slow. The low fall of the cement particles, which causes them to harden, allows this to be avoided or even dispersed when compacted crushed stones are present. Therefore, it is necessary to pay great attention to the timing of compaction
Keywords: Layer; concrete; compactor; mix